Tolvaptan treatment in an adult Fontan patient with protein-losing enteropathy: a serial 23Na-MRI investigation. (April 2021) - Moosmann, Julia; Toka, Okan; Linz, Peter; Dahlmann, Anke; Nagel, Armin M.; Schiffer, Mario; Uder, Michael; Cesnjevar, Robert; Dittrich, Sven; Kopp, Christoph
Background: Protein-losing enteropathy (PLE) is a severe complication of the univentricular Fontan circulation and associated with disturbances in salt and water homeostasis. Fontan patients with PLE have a poor prognosis, with increased morbidity and mortality. Due to limited therapeutic strategies, patients are often treated only symptomatically. Methods: We report our first experience of Tolvaptan (TLV) treatment in a Fontan patient with PLE, severe volume retention and hyponatraemia, refractory to conventional diuretic therapy. In addition to clinical parameters, we monitored drug effects including tissue sodium and volume status via serial 23 Na-magnetic resonance imaging ( 23 Na-MRI) and bioimpedance spectroscopy compared with age-matched controls. Results: 23 Na-MRI identified elevated tissue sodium, which decreased under TLV treatment, as well as volume status, while serum sodium increased and the patient's symptoms improved. During long-term treatment, we were able to differentiate between sodium and volume status in our patient, suggesting that TLV uncoupled body sodium from water. Conclusion: TLV in addition to loop diuretics improved clinical symptoms of PLE and lowered tissue sodium overload. Long-term effects should be further evaluated in Fontan patients.